A Multifunctional Integrated Metal‐Free MRI Agent for Early Diagnosis of Oxidative Stress in a Mouse Model of Diabetic Cardiomyopathy. Issue 7 (3rd January 2023) - Nie, Zhuang; Zhang, Kun; Chen, Xinyu; Wang, Jingxin; Gao, Huile; Zheng, Bingwen; Wu, Qihong; Guo, Yingkun; Liu, Xiangyang; Wang, Xu
Abstract: Reactive oxygen species (ROS) are closely associated with the progression of diabetic cardiomyopathy (DCM) and can be regarded as one of its early biomarkers. Magnetic resonance imaging (MRI) is emerging as a powerful tool for the detection of cardiac abnormalities, but the sensitive and direct ROS‐response MRI probe remains to be developed. This restricts the early diagnosis of DCM and prevents timely clinical interventions, resulting in serious and irreversible pathophysiological abnormalities. Herein, a novel ROS‐response contrast‐enhanced MRI nanoprobe (RCMN) is developed by multi‐functionalizing fluorinated carbon nanosheets (FCNs) with multi‐hydroxyl and 2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl groups. RCMNs capture ROS and then gather in the heart provisionally, which triggers MRI signal changes to realize the in vivo detection of ROS. In contrast to the clinical MRI agents, the cardiac abnormalities of disease mice is detected 8 weeks in advance with the assistance of RCMNs, which greatly advances the diagnostic window of DCM. To the best of the knowledge, this is the first ROS‐response metal‐free T2 ‐weighted MRI probe for the early diagnosis of DCM mice model. Furthermore, RCMNs can timely scavenge excessively produced ROS to alleviate oxidative stress. Abstract : This is a novel, metal‐free ROS‐sensitive MRI probe (RCMNs) for the early diagnosis of DCM in mice models by using the FCNs as functional carriers. Compared with conventional MRI agents, the cardiac abnormalities are detected 8 weeks in advance with assistance of RCMNs. Furthermore, RCMNs can timely scavenge excessively produced ROS to alleviate oxidative stress.